Peritoneal hydatidosis: An exceptional case report - Abdelillah El Bakouri; A Fatine; M Bouali; K El Hattabi; FZ Bensardi; A Fadil (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2022)
Hydatidosis is a cosmopolitan parasitic disease that presents a real public health problem, especially in endemic countries of which Morocco is part. The objective of the present work is to analyze the clinical, paraclinical, therapeutic, evolutionary, and prognostic aspects of disseminated peritoneal hydatidosis with multiple localization. Peritoneal hydatidosis represents the whole of the phenomena due to the seeding, essentially secondary, of the peritoneal serosa by Echinococcus Granulosus larvae. Peritoneal hydatidosis is characterized by its polymorphic symptomatology, and the diagnosis is based on a combination of epidemiological, clinical, biological, and imaging findings. We report a case of a particular form of peritoneal hydatidosis in the department of visceral surgery I of the ibn rochd hospital in Casablanca. Our patient was admitted for management of disseminated peritoneal hydatidosis. The clinical examination, apart from an epigastric crust, was unremarkable. The biological work-up showed a slightly disturbed liver balance and the hydatid serology was strongly positive. The preoperative diagnosis of HP was established by CT scan showing a supra- and sub-mesocolic peritoneal hydatidosis with a multi-cystic spleen and a liver with a type V segment V hydatid cyst measuring 4 cm by 6 cm. The treatment consisted of a total cystectomy of the hydatid cysts, almost 100 cysts with multiple peritoneal and parietal locations, one of which was fistulized in the skin, associated with a total splenectomy, retrograde appendectomy, and a disconnection of the cholecysto-duodenal fistula with duodenal closure and a retrograde cholecystectomy associated with a choledecotomy with the extraction of 3 stones at the level of the choledochus and drainage of the VBP by Kehr drain. The postoperative course was simple and the patient was discharged on the sixth day with adjuvant treatment with albendazole for three months. Through this observation and in the light of the data in the literature, we were able to insist in our present work on the diagnostic difficulties generated by this unusual location of the hydatid cyst as well as the considerable contribution of imaging (CT++) allowing both a positive and very precise topographic diagnosis. We were also able to focus on surgical treatment as an indispensable pillar of the management of this disease as well as the increasingly fundamental role of medical treatment, particularly in the prevention of recurrences.